2013
DOI: 10.1155/2013/484831
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics Study of Photocatalytic Activity of Flame-Made Unloaded and Fe-Loaded CeO2Nanoparticles

Abstract: Unloaded CeO2and nominal 0.50, 1.00, 1.50, 2.00, 5.00, and 10.00 mol% Fe-loaded CeO2nanoparticles were synthesized by flame spray pyrolysis (FSP). The samples were characterized to obtain structure-activity relation by X-ray diffraction (XRD), high-resolution transmission electron microscopy (HRTEM), Brunauer, Emmett, and Teller (BET) nitrogen adsorption, X-ray photoelectron spectroscopy (XPS), and UV-visible diffuse reflectance spectrophotometry (UV-vis DRS). XRD results indicated that phase structures of Fe-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 59 publications
0
17
0
Order By: Relevance
“…As the localized pH at the liquid-solid interface increases upon equilibration with its surrounding aqueous environment of pH 7.00, the concentration of the second major soluble species Ce(OH) 2+ increases. The same effect occurs for Ce(OH) 2 + and Ce(OH) 3 as the pH increases, although the concentrations of these species remain negligible. Therefore, these are the solutes that have the possibility of being present in the surrounding solution, which is at a nominal pH of~7.00.…”
Section: Speciation Diagramsmentioning
confidence: 64%
See 4 more Smart Citations
“…As the localized pH at the liquid-solid interface increases upon equilibration with its surrounding aqueous environment of pH 7.00, the concentration of the second major soluble species Ce(OH) 2+ increases. The same effect occurs for Ce(OH) 2 + and Ce(OH) 3 as the pH increases, although the concentrations of these species remain negligible. Therefore, these are the solutes that have the possibility of being present in the surrounding solution, which is at a nominal pH of~7.00.…”
Section: Speciation Diagramsmentioning
confidence: 64%
“…It is clear that the same progression of hydrolysis occurs for the conversion of Ce 3+ to Ce(OH) 3 . The greater stability of Ce 3+ is attributed to the lower field strength of Ce 3+ relative to that of Ce 4+ , which provides a lower driving force for hydrolysis [44], leading to the formation of Ce(OH) 2+ , Ce(OH) 2 + , and finally Ce(OH) 3 , although the pH range over which this occurs is smaller than for the Ce 4+ species. Furthermore, the inclusion of solid Ce(OH) 3 is based on similar experimental observations for the Pourbaix diagram of Hayes et al [43], which showed that Ce(OH) 3 precipitated when the pH exceeded~10.00.…”
Section: Speciation Diagramsmentioning
confidence: 79%
See 3 more Smart Citations